Research advances on renoprotective mechanism of SGLT-2 inhibitors in non-diabetic kidney disease - Feng Liu; Qing-mei Yang; Bo Pan; Xiao-hui Liu (Editorial Department of Journal of Clinical Nephrology, 2023)
Sodium-glucose linked transporter (SGLT-2) inhibitors are the most emerging glucose-lowering agents. Predominantly expressed in kidney, SGLT-2 is mainly distributed in upper part of proximal tubule. Mainly responsible for a reabsorption of filtered glucose, it accounts for over 80%-90% of glucose reabsorption. And SGLT-1 takes up the remainders. SGLT-2 inhibitors act at proximal tubule where they inhibit glucose and sodium reabsorption, thus enhancing urinary sugar excretion and lowering body glucose burden. Several studies have confirmed that SGLT-2 inhibitors might improve the prognoses of renal and cardiovascular disease in diabetics. Also there are significant protective effects on renal system of patients with non-diabetic kidney disease (NDKD). Therefore the induction protection mechanism of SGLT-2 inhibitors on non-diabetic chronic kidney disease (CKD) has attracted growing attention. This review summarized the latest researches of renoprotective mechanism of SGLT-2 inhibitors in NDKD.